Privatization and Regulation of Transport Infrastructure in the 1990s - Estache, Antonio (Washington, DC: World Bank, 2014)
Although the link between improved infrastructure services and economic growth is uncertain, it is clear that reforms aimed at creating competition and regulating natural monopolies establish an environment conducive to private sector participation, incentives for companies to strive for efficiency savings that can ultimately be passed on to consumers, and greater provision of services (such as faster roll-out of infrastructure or innovative solutions to service delivery for customers not connected to an existing network). In determining the form that infrastructure restructuring might undertake or the design of a regulatory agency, policymakers can generally benefit from a review of the experiences of other countries. A key element of any decision making process should be a review of how the various types of reform will affect the efficiency of the sector and whether they will increase private financing of its significant investment needs.